Development of an Integrated Islamic School Curriculum at The Ibnu Salam Nurul Fikri Islamic Boarding School Serang Banten - Yoseph Salmon (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to develop the integrated Islamic school curriculum at the Ibnu Salam Nurul Fikri Islamic Boarding School in Serang, Banten. This curriculum is designed by taking into account the characteristics of Islamic boarding schools, student needs, and adapting to the development of modern education and Islamic values. The research method used is research with a qualitative approach. Data was collected through interviews, observation, and documentation studies. Research participants involved teachers, students, and related parties at the Ibnu Salam Islamic Boarding School. The research results show that the developed curriculum can increase the relevance of learning material to student needs and the demands of current developments. Integrating Islamic values into every aspect of the curriculum provides a strong moral and ethical foundation for students. In addition, this curriculum encourages the holistic development of student competencies, including spiritual, intellectual, emotional, and social aspects. This research makes a positive contribution to the development of the integrated Islamic school curriculum in Islamic boarding schools, providing a model that can be adopted by similar educational institutions. The practical implications of this research can be a guide for schools in improving the quality of education and adapting the curriculum to Islamic boarding school characteristics and Islamic values. It is also hoped that the implementation of this curriculum can have a positive impact on forming a generation with morals and qualities to face future challenges.